Erich von Mendelssohn, Autor und früher Vermittler nordischer Literatur - Kreutzer, Gert (Folia Scandinavica Posnaniensia, 2016)
This contribution is to commemorate Erich von Mendelssohn (1887-1913), a gifted author and a translator of medieval and modern Scandinavian, especially Danish literature, who lamentably passed away at a very young age. It contains a short biography of von Mendelssohn and deals with his poetic (including a so far unknown poem) and prosaic works (Phantasten, Die Heimkehr, Nacht und Tag, Juliana) on one hand and his translations from Danish (works from J. P. Jacobsen, Thit Jensen, and Svend Fleuron) and Old (several sagas) and New Icelandic (Einar H. Kvaran) on the other.